Effect on hospital attendance rates of giving patients a copy of their referral letter: randomised controlled trial. Issue 7195 (22nd May 1999) - Hamilton, William; Round, Alison; Sharp, Deborah
Abstract: Objectives : To investigate whether sending patients a copy of their referral letter can reduce non-attendance at outpatient departments. Design : Blinded randomised controlled trial. Setting : 13 general practices in Exeter, Devon. Subjects : 2078 new consultant referrals from 26 doctors. Main outcome measures : Non-attendance at outpatient departments. Results : The doctors excluded 117 (5.6%) referrals, and 100 (4.8%) received no appointment. Attendance data were available for 1857 of the 1861 patients sent an appointment (99.8%). The receipt of a copy letter had no effect on the non-attendance rate: copy 50/912 (5.5%) versus control 50/945 (5.3%). Conclusion : Copy letters are ineffective in reducing non-attendance at outpatient departments.